Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Wachemo University - International Livestock Research Institute; Wachemo University (2021)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and WachemoUniversity. MOU signed on December 23, 2021, by Jimmy Smith, Director-General of ILRI and Habtamu Abebe, President of WachemoUniversity.